The development and applications of STEM ptychography using direct electron detectors - O'Leary, C (2020)
Since the introduction of direct electron detectors to scanning transmission electron microscopy (STEM), electron ptychography - a technique which utilises the interference in diffraction patterns to reconstruct the sample-induced phase changes of a transmitted electron wave - has significantly extended the capabilities of electron microscopy. However, a number of limitations to electron ptychography exist, namely the poor contrast transfer for low and high spatial frequencies to the phase reconstruction, and the relatively slow detector speeds used to acquire the ptychographic data (~ 1,000 fps). In this thesis, a number of strategies are introduced to further improve the robustness and dose-efficiency of focused-probe electron ptychography (FPP), after which several applications of FPP techniques are demonstrated.